Report on the second international workshop on the CCN family of genes. Issue 2 (1st April 2003) - Perbal, B; Brigstock, D R; Lau, L F
Abstract : For the second time, researchers from leading laboratories in the CCN field gathered in Saint-Malo, France, to participate in the Second International Workshop on the CCN family of genes. In addition to the regular research communications, meeting highlights included the inauguration of the first CCN newsletter (http://ccnnewsletter.free.fr ) and the recognition of the International CCN Society (http://www.ccnsociety.jussieu.fr ) as an important medium for the exchange of scientific knowledge and resources in the CCN field. Once more, the high quality of scientific communications and individual interactions set the stage for an extremely fruitful meeting.